Left ventricular global longitudinal strain as an indicator of myocardial injury in non-hospitalized COVID-19 survivors. (14th October 2021) - Hassan Abdelnabi, M; Abdelgawad, H; Saleh, Y; Almaghraby, A
Abstract: Introduction: The incidence of acute cardiac injury in COVID-19 patients is frequently subclinical and can be identified by cardiac magnetic resonance imaging. Left ventricular global longitudinal strain (LV-GLS) using two-dimensional speckle-tracking echocardiography (2D-STE) provides an accurate validated method for early detection of subclinical myocardial dysfunction. So far, long-term cardiovascular complications of COVID-19 are undetermined therefore several validated methods should be used for early diagnosis and intervention in those patients. Purpose: The aim of this work was to describe GLS as an indicator of myocardial injury in a case series of non-hospitalized COVID-19 patients complaining of persistent dyspnea after resolution of COVID-19 infection. Methods: A total number of 18 patients who were diagnosed with COVID-19 and were not indicated for hospital admission due to mild symptoms presenting with residual persistent dyspnea following COVID-19 infection resolution. Through clinical examination and standard 2D transthoracic echocardiography with STE emphasizing on LV-GLS was performed using Philips Epic - Qlab 10 software. Results: The mean age of the included patients was 37.44±6.33 years, the mean time from COVID-19 diagnosis was 48.1±15.45 days, all patients (100%) had persistent dyspnea grade II. The mean left ventricular ejection fraction (LVEF) was 62.9±3.46% while the mean LV-GLS was −15.55±2.16%. Clinical and echocardiographic data is presented in Table 1. Conclusion: In a case series of non-hospitalized COVID-19 survivors who complained of persistent dyspnea, GLS was low in comparison to the normally reported values of LV-GLS although they had normal LVEF indicating the persistence of myocardial injury even in mild cases of COVID-19 long after infection resolution. Further close follow-up of even mild and moderate COVID-19 survivors is certainly required to detect long-term cardiovascular sequelae. 2D STE with LV-GLS can be used as a readily available validated technique to detect early or persistent myocardial dysfunction succeeding COVID-19 infection. FUNDunding Acknowledgement: Type of funding sources: None.